The impact of economic and demographic changes in the city of Athens during the inter-war period (1922-1940). - Ntonou Efstratiadi, Anna; Tom, Nielsen; Dragonas, Panos (International Planning History Society Proceedings, 2016)
This paper is part of an ongoing research project which focuses its attention on the relation between the economic, political and social integration of migrants and refugees, the re-organization of the state, the legislative modernization and the economic policy during the interwar period in Greece. The key question of the research is in what different ways and procedures a city can be transformed under emergency conditions, such as that of the massive inflow of refugees and immigrants. In 1922 Greece, a state of 5 million inhabitants received a wave of refugees, the Greeks of Diaspora from Asia Minor, of such a scale (1.5 millions) that it overturned every population balance in the country. The presence of this large number of needy people was a problem whose solution was clearly beyond the limited resources of the Greek state, which was an underdeveloped country, financially exhausted by the Balkan wars, the Word War I and the Greco-Turkish war. The forced clustering of the Greeks within the limits of the Greek state paved the way for urban transformation and the development of the Greek society. The 53% of the refugees, who were of urban origin, settled in urban areas, especially in Athens. In this context Athens rapid urbanization created economic, social and governance challenges while simultaneously strained city’s infrastructure. The paper interprets and works with historical analysis, focusing on policies, economic structures, planning policies and the actual physical urban transformation of Athens, combining methods from architecture and economics. It examines how the new urban structure of Athens adjusted in order to redress social, economic and urban imbalances. The external borrowing, the inflow of foreign capital, due mainly to the international economic downturn, and the development of an informal economy showed the capacity of Athens to survive, to adapt, and to grow despite the stresses and acute shocks it experienced. The human geography of the Athens basin, was so radically transformed that new modes of land and housing allocation emerged. The urban planning of Athens and consequently the type of city that emerged, should be attributed to the inability of the state to impose on landowners regulations for the sound planning, organization and construction of urban real estate. The uncontrolled expansion of the city reflected the regular and irregular practices in architecture and housing development, which were expressed through modernism and legislation on one hand and modern vernacular on the other. The purpose of this paper is to develop a framework for understanding the response of a contemporary city to internal and external challenges. Based on comparative analysis of Athens urban resilience we can identify concepts that will be used to begin to understand case studies of other cities in the modern era.